Implementasi k-Means Untuk Sistem Informasi Penyebaran Penyakit Epidemi Di Kota Malang - Dyas Irvan Masruri; Sugeng Widodo; Febry Eka Purwiantono (LPPM STIKI MALANG, 2021)
Epidemic is a disease that spreads very quickly in a large area and causes many victims who require intensive care and attention in areas affected by the epidemic quickly and appropriately. There are many infectious diseases that occur in Malang City, one of which is Dengue Hemorrhagic Fever (DHF). The availability of fast and clear information can help the Malang City Health Office in making decisions regarding the prevention of epidemic diseases. So the researchers created a geographic information system for the spread of epidemic diseases using a web-based k-means algorithm that will present information related to epidemic diseases in the city of Malang. To calculate the k-means algorithm, criteria are needed as variables and in this study the criteria taken are the number of patients in each kelurahan for a year. From these criteria, 3 groups will be declared using C1 as a safe area, C2 as a moderate area, and C3 as a vulnerable area. The results of the grouping are then presented in the form of a map of Malang City with the help of MapBox. In the map, group C1 is marked in green, group C2 is in yellow, and group C3 is in red